Prevalensi dan Intensitas Parasit pada Udang Kaki Putih (Litopenaeus vannamei) di Kecamatan Teluk Mengkudu Kabupaten Serdang Bedagai - Rania Febriyola Siregar; Syukriah (BIOEDUSAINS:Jurnal Pendidikan Biologi dan Sains, 2025)
This study aimed to identify the types of parasites, prevalence, and intensity of parasitic infections in vannamei shrimp (Litopenaeus vannamei) in Teluk Mengkudu District, Serdang Bedagai Regency. The research employed a descriptive method using random sampling techniques at two traditional shrimp ponds. Shrimp samples were examined at the Zoology Laboratory, Faculty of Science and Technology, UIN Sumatera Utara. The observed organs included walking legs, swimming legs, and the tail. The results showed that three types of ectoparasites infected vannamei shrimp, namely Zoothamnium sp., Epistylis sp., and Vorticella sp. Water quality parameters indicated temperatures of 28–28.2°C, pH of 7.75–8.23, ammonia levels of 1.436–2.732 mg/L, nitrate levels of 1–1.1 mg/L, nitrite levels of 0.14–0.95 mg/L, dissolved oxygen of 0.91–3.56 mg/L, and salinity of 15.53–21.63‰. The conclusion shows that the highest prevalence was found in Zoothamnium sp. at 26%, while the highest intensity was 3.87 individuals per shrimp.   Keywords: Ectoparasite, Intensity, L. vannamei, Prevalence